Penerapan Model Project Based Learning (PJBL) pada Materi Sistem Persamaan Linier Dua Variabel untuk Meningkatkan Hasil Belajar Siswa - Irawati, Tri Novita; Anisatul Maghfiroh, Rizka; Rohman, Syaifur (FKIP Universitas Islam Jember, 2025)
The purpose of this study was to describe student learning outcomes during the application of the Project Based Learning (PjBL) learning model on the Two Variable Linear Equation System (SPLDV) material. This study used classroom action research where this PTK was implemented in the form of repeated cycles which included: (1) planning, (2) implementation of actions, (3) observation, and (4) reflection. The first cycle was used as a basis for conducting reflection and evaluation which would guide the implementation of the next cycle. Tests, observations, interviews, and documentation were data collection methods. Student learning outcomes increased where from the pre-cycle to cycle II showed that PjBL can be a relevant and useful method in learning mathematics. Where in cycle I the completion value was 67% and in cycle II the completion value was 90%. From these data, there was an increase in student learning outcomes, thus proving that the use of the Project Based Learning learning model can improve student learning outcomes.